DAMPAK KEBERADAAN BADAN USAHA MILIK DESA TERHADAP KEBERSIHAN LINGKUNGAN DESA TAENG KECAMATAN PALLANGGA KABUPATEN GOWA - Nurasyah, Nurasyah; Fatmawati, Fatmawati; Yusuf, Muhammad (Universitas Muhammadiyah Makassar, 2023)
This study purposed to find out the impact of Village Owned Enterprises (BUMDes) efforts in overcoming environmental cleanliness in Taeng Village and to measure the impact of BUMDes efforts on changes in environmental conditions in Taeng Village, Palangga District, Gowa Regency. This study used a quantitative approach to survey methods by distributing questionnaires to 99 respondents from the Taeng Village community. The sampling technique used random sampling. Data was collected by observations, questionnaires, and documentation. The data analysis technique used a simple linear regression analysis technique with the help of SPSS version 26.0 software. The results of the Simple Linear Regression Test, the constant of 13,036. It meant that the consistent value of the BUMDes effort variable was 13,036. The regression X coefficient of 0.222 stated that for every 1% addition of BUMDes efforts, the value of changes in environmental conditions increased by 0.222. The regression coefficient was positive and the magnitude of the impact of BUMDes efforts was 0.503 or 50.3% seen from the R-square test so it could be said that the impact of BUMDes efforts on changes in environmental conditions was positive (Impact).